PENGENALAN PENGGUNAAN SIMULASI PENGECORAN BAGI USAHA COR LOGAM DI PALEMBANG - Irawan Malik; Moch. Yunus; Dwi Arnoldi; Yogi Eka Fernandes (Politeknik Negeri Sriwijaya, 2021)
Problems in metal casting include, among others, air cavity defects caused by use of pour plate and descending channel models which are directly used in sand molds; air or gas from sand mold or aluminum scrap liquid metal cannot escape through cavity between the sand grains during pouring process; river sand is in the form of crystalline sand grains which can affect fire resistance and low permeability in sand molds, consequently requiring large amounts of binder; and water content in river sand for making sand molds is less than 1.5% - 8% as a result, clay will experience a lack of binding power in the sand. Departing from the above problems, it is necessary to pay attention to design stages, especially in e field of casting product design, which currently uses a lot of software that can support businesses, such as Solidworks Computer Aided Design - Computer Aided Manufacturing software and casting simulation software such as Altair Inspire cast. Design of cast objects and simulation in preparation for making molds and core castings using Solidworks and Altair Inspire Cast software aims to obtain accuracy of the cast objects so that they do not require much finishing work and the simulation of casting process is expected to reduce casting failures as described. Essence of implementation of community service programs through (additional) assignment schemes for small industries Mandiri of metal cast in Palembang is how to provide theoretical knowledge of designing cast objects using CAD software and simulate the casting process which is usually used for students of study program D-IV in Mechanical Engineering of Production and Maintenance (TMPP) - State Polytechnic of Sriwijaya. to find out the best design model and casting process so as to minimize casting defects.